An Analysis of Student Performance in Understanding and Responding to Short Functional Texts - Lukman B; Sukri Adani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the ability of eighth-grade students at MTsN 3 Aceh Barat Daya to respond accurately to short functional texts containing common social expressions in English and to identify which categories are most and least effectively mastered. Five communicative functions were examined: expressing gratitude, apologizing, giving compliments, offering help, and greeting. Using a quantitative descriptive design, data were collected from 42 students through a 20-item dialogue-based multiple-choice test. Descriptive statistical analysis was employed to determine the mean, accuracy percentage, standard deviation, and score distribution per category. The results revealed that students achieved an average accuracy of 82.5% (median = 18.5/20), indicating generally good ability, though performance varied considerably. The highest proficiency was observed in giving and responding to compliments (95% accuracy), while acknowledging mistakes showed the lowest performance (79% accuracy), possibly due to cultural norms and limited exposure to authentic usage. Variation in scores was also linked to vocabulary range, interaction experience, and confidence. These findings suggest that English instruction should incorporate culturally sensitive categories, especially those less familiar to students, through authentic conversation, role-play, and interactive technology, with differentiated support for lower-performing learners.